Ankle flexor/extensor strength and muscle density are complementary determinants of balance during dual‐task engagement: The ankle quality study. Issue 1 (12th January 2023) - Wong, Andy K. O.; Fung, Hugo J. W.; Pretty, Steven P.; Laing, Andrew C.; Chan, Adrian H.; Mathur, Sunita; Zabjek, Karl; Giangregorio, Lora; Cheung, Angela M.
Abstract: Background: This study investigated relative contributions of ankle flexor torque, muscle size, and density on balance and falls. Methods: Men and women ≥50 years of age completed a peripheral quantitative computed tomography scan of the mid‐leg to quantify muscle density (MD) and cross‐sectional area; Biodex dynamometry to evaluate maximal isometric ankle flexor torque; and a single‐leg balance test on a force platform with/without eyes closed and cognitive task. Ankle flexor torque, muscle size, and density individually, together, or as interactions were examined for associations with balance (mean step duration, steps/trial) in general linear models, or with falls in Poisson regression, adjusting for age, sex, BMI, glucocorticoid use, osteoarthritis, and physical activity. Visuo‐cognitive conditions were compared. Results: Among 105 participants (age: 63.3 ± 9.9 years, BMI: 25.8 ± 5.4 kg/m 2, 77.1% female), 41.8% experienced ≥1 fall in the last year. Balance on one leg was dependent on ankle flexor torque when eyes were open ( r = −0.220 to −0.284) and on having leaner mid‐leg muscles when eyes were closed ( r = −0.123 to −0.142); cognitive challenge blunted these correlations. Individuals with leaner muscles tended to rely more on plantarflexors than dorsiflexors. A 2% lower step‐free fraction in the eyes‐closed paradigm associated with having 1 additional fall [−0.701(−1.235, −0.167)], but neither torque, muscle density, nor size related to number of falls. Conclusions: Among ambulatory adults, ankle flexor torque and muscle density showed an interactive influence on balance that depended on visuo‐cognitive input. The complementary roles of torque and muscle density on balance suggest redundancy is important under dual‐tasking conditions.